PELATIHAN MANAJEMEN REKAM MEDIS DAN INFORMASI KESEHATAN PETUGAS REKAM MEDIS SEBAGAI CLINICAL INSTRUCTUR (CI) DI PUSKESMAS KAB.CIREBON - Khasanah, Lina (Indonesian Journal of Health Information Management Services, 2024)
Education and training is one of the efforts to increase human resources and a series of activities or efforts that are carried out continuously, gradually and integratedly. The training was carried out to develop Clinical Instructor competency in organizing student clinical practice activities at community health centers. The limited knowledge of Clinical Instructors in terms of competencies that must be achieved by practical students influences the implementation of clinical practical learning and when giving assessments. One of the competencies that must be achieved during clinical practice is the basic management of medical records. This research aims to increase CI's knowledge and competence in implementing clinical practice guidance for students. The method used is training with several stages of activities, namely competency identification analysis in the form of training system design, then implementation of activities, and evaluation. The increase in competency is proven by an increase in post test results from an average pre test score of 71.59 and an average post test result of 87.73. The evaluation results of training implementation can be assessed on 4 scales, namely training implementation, speakers, materials, etc. Each scale has an average value of 3.5, these results prove that the training implementation process is in the good category. Implementation of training can improve the competency of medical record officers as Clinical Instructors in administering clinical practice students at community health centers.